2002
DOI: 10.1111/j.1532-849x.2002.00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis on dental implant–supported prostheses without passive fit

Abstract: Purpose: The purpose of this study is to use finite element analysis to investigate the effect of misfit prostheses, cantilever prostheses, and various occlusal forces on the stress distribution in the prostheses, implant components, and surrounding bone.Materials and Methods: Two 3-dimensional finite element models were constructed: (1) a 2-implant-supported, 2-unit fixed partial denture and (2) a 2-implant-supported, 2-unit fixed partial denture with a distal cantilever. Variations of the standard finite ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
1
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 12 publications
4
82
1
9
Order By: Relevance
“…The retention screw of the molar presented high stress values, which were observed in the long axis and probably caused by tensile forces. A considerable increase in stress was observed in the framework, porcelain veneer, and retention screw proportional to the increase in misfit, which is in agreement with previous studies (8,11,18,21). It has been suggested that these structures are more sensitive to a lack of passive fit and are directly responsible for clinical failures such as loosening or fracture of the abutment or prosthetic screw and fracture of the framework or veneers (18) due to asymmetric contact among the various components of the system (28).…”
Section: Figsupporting
confidence: 81%
See 3 more Smart Citations
“…The retention screw of the molar presented high stress values, which were observed in the long axis and probably caused by tensile forces. A considerable increase in stress was observed in the framework, porcelain veneer, and retention screw proportional to the increase in misfit, which is in agreement with previous studies (8,11,18,21). It has been suggested that these structures are more sensitive to a lack of passive fit and are directly responsible for clinical failures such as loosening or fracture of the abutment or prosthetic screw and fracture of the framework or veneers (18) due to asymmetric contact among the various components of the system (28).…”
Section: Figsupporting
confidence: 81%
“…The changes in vertical misfit showed a considerable influence on the stress values in peri-implant bone tissue; this fact was also observed in other FEA reports (8,17). Previous studies performed in primates (9) and rabbits (10,30,31) evaluated the consequences of different levels of vertical misfit on the peri-implant bone tissue.…”
Section: Figsupporting
confidence: 70%
See 2 more Smart Citations
“…A revisão da literatura mostra que grande parte dessas complicações estão relacionados aos parafusos protéticos, responsáveis pela fixação entre a prótese aos implantes (McGLUMPHY;MENDEL;HOLLOWAY, 1998;HOLLWEG, 2000;DUYCK et al, 2001;KUNAVISARUT et al, 2002).…”
Section: Introductionunclassified